ViGLAD: Vision Graph Neural Networks for Logical Anomaly Detection - Firas Zoghlami; Dena Bazazian; Giovanni L. Masala; Mario Gianni; Asiya Khan (IEEE Access)
Quality inspection is an industrial field with a growing interest in anomaly detection research. An anomaly in an image can either be structural or logical. While structural anomalies lie on the image objects, challenging logical anomalies are hidden in the global relations between the image components. The proposed approach, Vision Graph based Logical Anomaly Detection (ViGLAD), uses the graph representation of an image for logical anomaly detection. Defining an image as a structure of nodes and edges leverages new possibilities for detecting hidden logical anomalies by introducing vision graph autoencoders. Our experiments on public datasets show that using vision graphs enhances the performance of state-of-the-art teacher-student-autoencoder neural networks in logical anomaly detection while achieving robust results in structural anomaly detection.